A compound control method for the rejection of spatially periodic and uncertain disturbances of rotary machines and its implementation under uniform time sampling. (August 2016) - Huo, Xin; Tong, Xin-Gang; Liu, Kang-Zhi; Ma, Ke-Mao
Abstract: In this paper, a compound control which combines a spatial internal model with a linear extended state observer (LESO) is proposed for continuously rotating machines. It is implemented digitally based on a uniform time sampling. An angular position-based internal model is synthesized in the spatial domain to suppress the spatially periodic disturbances existing in rotary machines, which is actuated with a fixed sampling period by introducing the angular position to the internal model in real-time. Further, an LESO is designed to estimate non-periodic disturbances and uncertain dynamics acting on the system so as to reduce the steady state error of the position output with respect to ramp angular position reference input. Comparisons and experimental results are presented to illustrate the feasibility and effectiveness of the compound control method. Abstract : Highlights: A compound control method is proposed. Spatially periodic disturbances are rejected effectively by means of inserting spatial internal models. LESO is applied to reduce the steady state error and estimate angular velocity of the machine. The proposed compound controller is implemented with fixed time sampling interval.